Evaluation of the cytotoxicity (HepG2) and chemical composition of polar extracts from the ruderal species Coleostephus myconis (L.) Rchb.f. Issue 13 (3rd August 2017) - Bessada, Sílvia M. F.; Barreira, João C. M.; Santos, J.; Costa, Carla; Pimentel, Filipa B.; Bessa, Maria João; Teixeira, João Paulo; Oliveira, M.Beatriz P.P.
ABSTRACT: Coleostephus myconis (L.) Rchb.f. (Asteraceae) is a highly disseminated plant species with ruderal and persistent growth. Owing to its advantageous agronomic properties, C. myconis might have industrial applications. However, this species needs to be comprehensively characterized before any potential use. In a previous study, the phenolic composition and antioxidant activity of different C. myconis tissues were characterized. This investigation was extended to examine the cytotoxic potential of selected plant tissues (flowers and green parts) using a HepG2 cell line by utilizing the lysosomal neutral red uptake assay or mitochondrial (3-(4, 5-dimethylthiazolyl-2)-2, 5-diphenyltetrazolium bromide assay. In addition, the macronutrients content, lipophilic compounds (fatty acids, tocopherols), and amino acids were also determined. C. myconis flowers were used in the senescence stage, which was previously identified as the stage that presented maximal phenolic content and highest antioxidant activity. In contrast, stems and leaves were employed due to their high biomass proportion. Regarding cytotoxicity, mitochondrial and lysosomal damage was only significant when HepG2 cells were exposed to the highest extract concentrations (stems and leaves, 0.9 mg/ml; senescent flowers, 0.3 mg/ml). Chemically, the senescent flowers were mostly characterized by their high levels of fat, amino acids (especially threonine), oleic acid, β-, and γ-tocopherol, while stems and leaves contained high concentrations of carbohydrates, linolenic acid, and α-tocopherol. In general, these results provide information regarding the threshold concentrations of C. myconis extracts that might be used in different applications without toxicity hazards.